Analytical tools for elucidating the biological role of melatonin in plants by LC-MS/MS - Gomez, Federico Jose Vicente (2013)
Melatonin presence in higher plants was recently discovered and the knowledge of its function in vivo is limited. Several studies have recently shown the occurrence of melatonin and related compounds in grapes and wines. The analysis of melatonin in plants and foods represents a highly challenging task due to its wide concentration range, the difficulty in the selection of the extraction solvents because of its amphipathic nature, and the fact that it reacts quickly with other matrix components. Thus, sample processing factors, preparation/cleanup procedures and chromatographic/detection parameters such as HILIC and reverse phase (C8 and C18) chromatographic modes, electrospray ionization and atmospheric pressure chemical ionization in both negative and positive modes were evaluated. Taken together, we have demonstrated that optimal conditions were quite different for each of the matrices under study. A sonication mediated- extraction step was necessary for grape skin (100% v/v methanol) and plant tissues (50% v/v methanol), while wine and must required a solid phase extraction preconcentration step. HILIC chromatography-(+)APCI ionization was better for melatonin standards, while C8-(+)APCI was the best choice for grape skin and C18-(+ESI) was suitable for wine. On the other hand, C8-(+)ESI was the most appropriate for vegetal tissues of Arabidopsis thaliana. Proposed methods were validated, the limits of detection were in the low picograms levels range. The optimized approaches were applied to the determination of melatonin and its isomer in different vegetal/food samples; levels found within the range: 4.9?440 ng g−1.